Validitas Syar’i dalam Ruang Maya: Analisis Fikih atas Praktik Ta’aruf Digital - Nur Halimah; Asfar Hamidi Siregar (Jurnal Pustaka Cendekia Pendidikan, 2025)
It is undeniable that technological developments have brought major changes to the social and religious realms of human life. One of them is the phenomenon of digital taaruf which is now a trend among the younger generation as an alternative to finding a life partner through online platforms. So it is interesting to study the validity of the sharia in this practice. This study aims to analyze the concept of digital taaruf from the perspective of fiqh munakahat. Using a descriptive qualitative approach, data was obtained through literature studies and analysis of several digital ta'aruf platforms in Indonesia. The results of the study show that despite differences in services and costs, the three platforms still prioritize the principles of Islamic law such as maintaining manners, involving third parties who can certainly avoid slander for prospective couples who use this service. In the view of fiqh munakahat, digital ta'aruf is acceptable as long as it is in accordance with sharia values. Thus, digital ta'aruf is a form of actualization of the concept of introduction in Islam that is relevant to the development of the times.